2020
DOI: 10.1186/s12894-020-00685-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Retzius-sparing robot-assisted laparoscopic radical prostatectomy vs standard robot-assisted radical prostatectomy: a meta-analysis

Abstract: Background: To compare the postoperative continence and clinical outcomes of Retzius-sparing robot-assisted laparoscopic radical prostatectomy (RS-RALP) with non-RS RALP for patients with prostate cancer. Methods: We searched PUBMED, EMBASE and the Cochrane Central Register from 1999 to 2019 for studies comparing RS-RALP to non-RS RALP for the treatment of prostate cancer. We used RevMan 5.2 to pool the data. Results: A total of eight studies involving 1620 patients were included in our meta-analysis. No signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Umari et al found that at 12 months, there was no benefit to Retzius-sparing RARP over anterior approach [19], where as we found that Retzius-sparing RARP continued to provide improved pad-free continence at 12 months. Overall, this paper supports recent literature reviews and meta-analysis [20,21] and [17] suggesting that a Retzius-sparing approach demonstrates better continence rates compared to the standard approach to RARP with no negative effect on oncological outcomes at 12 months.…”
Section: Discussionsupporting
confidence: 85%
“…Umari et al found that at 12 months, there was no benefit to Retzius-sparing RARP over anterior approach [19], where as we found that Retzius-sparing RARP continued to provide improved pad-free continence at 12 months. Overall, this paper supports recent literature reviews and meta-analysis [20,21] and [17] suggesting that a Retzius-sparing approach demonstrates better continence rates compared to the standard approach to RARP with no negative effect on oncological outcomes at 12 months.…”
Section: Discussionsupporting
confidence: 85%
“…To our knowledge, our meta-analysis is the most up-to-date and comprehensive. Due to the inclusion of several recent high-quality works of literature ( 19 24 ), we have obtained some more stable results in some outcome indicators that were different from the previous meta-analyses ( 18 , 29 , 30 ). In addition, we are the first study to include the PLND rate in the meta-analysis, and also the first study to conduct the subgroup analysis based on the population.…”
Section: Discussionmentioning
confidence: 73%
“…To our knowledge, our meta-analysis is the most up-to-date and comprehensive. Due to the inclusion of several recent high-quality works of literature (19)(20)(21)(22)(23)(24), we have obtained some more stable results in some outcome indicators that were different from the previous meta-analyses (18,29,30).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Furthermore, stretching of Hesselbach's ligament contributes to a decrease in strength of the internal ring [2,8,9]. Minimally invasive and Retzius-sparing techniques seem to decrease the risk of an inguinal hernia by minimizing damage to the region of the myopectineal orifice (MPO) [6,9,21]. Several prophylactic measures have been proposed to minimize the risk of inguinal hernia after transabdominal prostatectomy, including a ligation and transection of the processus vaginalis, blunt dissection of the peritoneum close to the internal ring with an isolation of the spermatic cord, or the placement of additional stitches to close the internal ring [6,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%